Preservation of Animal Cadavers with a Formaldehyde-free Solution for Gross Anatomy (2018)
ABSTRACT: Motivated by the current health safety regulations at Universidad de Antioquia, our laboratory changed the animal cadavers preserving solution based on formaldehyde, methanol, glycerin and phenol to a formula based on 85% ethanol, 10% glycerin, and 5% benzalkonium chloride. A total of 33 donated cadavers were preserved with this formula so far: 4 goats, 16 dogs, 3 cats and 10 bovine fetuses. Red and blue latex dyes were injected into the vascular systems. Small cadavers were first injected with latex, followed by muscular and intracavitary injection with the preservation fluid and immersion in 96% ethanol. Large cadavers were vascularly injected, wrapped in plastic bags and vascularly repleted with latex during the next 8 days. Samples were taken for microbiological analysis from 3 cadavers: 1 cadaver wrapped with plastic for 2 months, 1 cadaver immersed for 4 months, and 1 cadaver after 15 days of perfusion. The first way to preserve cadavers was more time-consuming, but it rendered cadavers with a more thorough distribution of latex on small arteries and veins. An enhanced flexibility of joints and tissues promoted an easier dissection process, even of the most distal regions, allowing the movement of tendons along their sheaths. Also, a better color preservation was observed in spite of a darkening after the tissues were exposed to the air. There was no gross evidence of decay from bacterial or fungal growth, and the cultures were negative. The most important advantage of this formula is its lower toxicity and cost.